Analysis of the influence of surface deformation on the stability of overhead transmission lines and countermeasures - Xiaokai Meng; Siqing Xu; Fan Hu; Shuai Wang; Zhumao Lu (AIP Advances)
This study analyzed the impact of surface deformation on the stability of overhead transmission lines and proposed corresponding countermeasures. The research first explored the mechanical effects of tower tilt, displacement, and suspension point changes caused by surface deformation on transmission lines. These effects include redistribution of conductor tension and deviation of insulator strings. Through mathematical models and engineering approximations, the specific effects of tower foundation settlement and horizontal displacement along the line direction on the operating conditions of various levels of overhead lines were analyzed in detail. The research has shown that surface deformation can cause suspension points to become stress concentration areas, leading to deformation or damage of suspension plates and their fixing components, thereby affecting the stability of the power system. To accurately assess these impacts, it is recommended to use high-precision measuring instruments for regular data collection and analysis. In addition, this study emphasizes the importance of considering the role of additional forces in structural design and selecting tower materials with sufficient strength, stiffness, and corrosion resistance. Finally, this paper proposes a series of maintenance and adjustment measures, such as re-tensioning wires, adjusting tower positions, or adding additional support structures, to ensure the safe and stable operation of the line.